Determinants of Disaster Preparedness among Healthcare Workers in the Sukabumi Coastal Area: The Mediating Role of Resilience and Perception - Johan Budhiana; Rosliana Dewi; Fera Melinda; Maria Yulianti; Waqid Sanjaya; Yohan Frans Unmehopa (Media Publikasi Cendekia Indonesia, 2026)
The preparedness of healthcare workers to respond to disasters in coastal areas is a crucial aspect that must be optimally developed. This preparedness is influenced by various factors, such as government policy, perceptions and resilience. This study aims to analyse the direct and indirect effects of government policy, perceptions and resilience on the preparedness of healthcare workers to respond to earthquakes and tsunamis in the coastal areas of Sukabumi Regency. This study employs a quantitative design with a cross-sectional approach involving 512 respondents, selected using total sampling. Data were collected via a structured questionnaire measuring government policies, perceptions, resilience, and disaster preparedness. All instruments underwent validity and reliability testing and were found to be valid and reliable. Data analysis was conducted using the SEM-PLS method to test the direct and indirect relationships between variables. The results of the study indicate that there is a significant direct effect of government policy on disaster preparedness (O=0.348, t=7.265, p=0.000), perceptions of disaster preparedness (O=0.296, t=7.785, p=0.000), and resilience to disaster preparedness (O=0.227, t=5.870, p=0.000). There is an indirect effect of government policy on disaster preparedness via perception (O=0.176, t=7.206, p=0.000), government policy on disaster preparedness via perception and resilience (O=0.116, t=2.120, p=0.036), and government policy on disaster preparedness through resilience (O=0.118, t=2.113, p=0.040). Based on the modelling results, government policy, perception, and resilience were identified as important determinants of healthcare workers’ disaster preparedness in the coastal areas of Sukabumi Regency. These findings highlight the need to strengthen disaster training, improve understanding of disaster policies, and enhance the psychological resilience of healthcare workers to support preparedness.